2007
DOI: 10.1002/jcp.20958
|View full text |Cite
|
Sign up to set email alerts
|

Amelioration of inflammation, angiogenesis and CTGF expression in an arthritis model by a TSP1‐derived peptide treatment

Abstract: Both inflammation and angiogenesis were decreased after TSP1-derived peptide treatment indicating a potential pathway by which TSP1 interaction with neutrophils induces CTGF in RA affected tissues.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 37 publications
(55 reference statements)
0
26
0
Order By: Relevance
“…This report is the first to show that ICs in the sera of RA patients contain TSP-1, and the IC may be a promising marker for RA. Recent studies have suggested that the TSP-1/ transforming growth factor/connective tissue growth factor pathway plays an important role in angiogenesis and erosive arthritis lesions (13,14 ). Although platelet factor 4 (PF4) was less sensitive (52.4%; 95% CI, 30%-75%) than TSP-1, our method also specifically detected PF4 or a variant incorporated into CICs in RA patients for the first time (Table 1, Fig.…”
Section: Discussionmentioning
confidence: 81%
“…This report is the first to show that ICs in the sera of RA patients contain TSP-1, and the IC may be a promising marker for RA. Recent studies have suggested that the TSP-1/ transforming growth factor/connective tissue growth factor pathway plays an important role in angiogenesis and erosive arthritis lesions (13,14 ). Although platelet factor 4 (PF4) was less sensitive (52.4%; 95% CI, 30%-75%) than TSP-1, our method also specifically detected PF4 or a variant incorporated into CICs in RA patients for the first time (Table 1, Fig.…”
Section: Discussionmentioning
confidence: 81%
“…The role of TSP-1 in RA and angiogenesis is described above [50]. In a recent study [50], a TSP-1-derived peptide suppressed synovial inflammation and angiogenesis in a rat arthritis model.…”
Section: Further Advances In Angiostatic Therapymentioning
confidence: 96%
“…In a recent study [50], a TSP-1-derived peptide suppressed synovial inflammation and angiogenesis in a rat arthritis model.…”
Section: Further Advances In Angiostatic Therapymentioning
confidence: 98%
See 1 more Smart Citation
“…These properties might be due in part to specific secreted factors, including some types of cytokines and growth factors. For instance, it has been reported that thrombospondin-1, 2 (TSP-1, 2) functions as an anti-inflammatory factor in RA by suppressing production of proinflammatory mediators such as IFN-γ and TNF-α, inducing depletion of synovium residing T cells and reducing infiltration of monocytes/macrophages in articular tissues [18,19] . In this fashion, chondrogenic differentiation and paracrine actions might be involved in replacement of damaged cartilage tissues and stimulation of the regeneration process.…”
Section: Hucb-mscs For Cartilage Regenerationmentioning
confidence: 99%